Implementasi Model Ekobis 2-3-5 : Investasi Sosial Bisnis Bagi Hasil Penggemukan Domba Di Desa Bangunkarya Kecamatan Langkaplancar Kabupaten Pangandaran - Sondi Kuswaryan; Iim Siti Karimah; Tri Indri Hardini (Universitas Pendidikan Indonesia, 2023)
This community service activity was carried out in Bangunkarya Village, Langkaplancar District, Pangandaran Regency, with the aim to increasing the livelihood degree of rural communities. The activities carried out are increasing the capacity and participation of sheep farmers for the Ecobis 2-3-5 Program, which is a profit-sharing program for fattening sheep to meet the needs of sacrificial animals. Financial capital for fattening sheep was collected from participants using the Crowd Funding Pattern. The main targets of this activity are sheep farmers and Sheep Farmes Groups as implementers of the Ecobis 2-3-5 program. The results of this activity are (1). The Ecobis 2-3-5 Program is able to return investments accompanied by an added value of 18 percent for investors. (2). There has been a change in mindset, attitude patterns and behavior patterns towards the importance of sheep in people's livelihoods, followed by actions in efforts to improve sheep farming. (3). There has been an increase in the interest of breeders to participate in the Ecobis 2-3-5 program. Therefore, a greater investment value is needed, so that the value of the benefits can be felt by more farmer households.